Direito, Estado e religião: o casamento civil nos primórdios do regime republicano brasileiro - Luisa Cristina de Carvalho Morais (2016)
The wedding discipline in the early days of the Brazilian republican regime deserves careful consideration. The claim for the civil marriage emerged during the Empire, intensifying with the increase of non-Catholic population in the country. Despite the demand for legislation that could recognize other forms of marriage, the progress was slow. It is possible to identify five moments related to the topic. Initially, the only valid marriage was the Catholic. In a second moment, still during the Empire, there was the recognition of effects to marriages performed according to the rites of other religions. In a third moment, already during the Republic, the civil marriage was implemented as the only juridically valid option. In a forth moment, during the Temporary Government, there was the imposition of civil marriage precedence over the religious. In a fifth moment, the Constitution of 1891 did not bring the obligatory precedence of the civil marriage. This research investigates the intense and complex time of consolidation of the Brazilian republican regime. The study of this period is marked by the differentiation, made by Fernando Catroga, between laicity, laicism and secularization. By investigating the legal treatment given to marriage and its meanings, the research seeks to verify if the posture of the State reflected, at some point, a laic or even laicistic behavior, as well as what kind of influence contributed to the decision making.